2022
DOI: 10.1186/s12978-022-01495-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel homozygous mutation in the PADI6 gene causes early embryo arrest

Abstract: Background It has been proved that mutations in the PADI6 gene can cause early embryo arrest. This study describes a newly discovered mutation in PADI6 that expands the genetic spectrum of early embryo arrest. Methods Peripheral blood of a patient diagnosed with early embryo arrest was collected for whole-exome sequencing. Sanger sequencing was performed to confirm this mutation. The effects of the variant were investigated in human embryonic kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Since the evaluation of the phenotype associated with EDA in any situation except recurrent IVF failure (RIF) is difficult and accessibility to it in the natural environment is not possible, the genetic cause of EDA in humans is not fully understood. According to previous studies, we can point to chromosomal abnormalities, and single-gene mutations in some genes such as NLRP2 9 , NLRP5 9 , FBXO43 10 , PADI6 11 , Btg4 12 , CDC20 13 , MOS 14 , 15 , and ACTL7A 16 as the genetic causes of EDA. This process is also associated with aberrant regulation of several signaling pathways such as the Wnt and TGFβ signaling pathways 17 .…”
Section: Introductionmentioning
confidence: 98%
“…Since the evaluation of the phenotype associated with EDA in any situation except recurrent IVF failure (RIF) is difficult and accessibility to it in the natural environment is not possible, the genetic cause of EDA in humans is not fully understood. According to previous studies, we can point to chromosomal abnormalities, and single-gene mutations in some genes such as NLRP2 9 , NLRP5 9 , FBXO43 10 , PADI6 11 , Btg4 12 , CDC20 13 , MOS 14 , 15 , and ACTL7A 16 as the genetic causes of EDA. This process is also associated with aberrant regulation of several signaling pathways such as the Wnt and TGFβ signaling pathways 17 .…”
Section: Introductionmentioning
confidence: 98%
“…Using exome sequencing of DNA from 606 women with this type of infertility, the authors identified deleterious compound heterozygous or homozygous variants in karyopherin subunit α7 (KPNA7) in ten (1.7%) families. The genetic burden of KPNA7 matches that of PADI6, the most frequently implicated maternal gene in preimplantation embryo arrest (8,9). This result revealed the requirement of another class of proteins, karyopherins, for early human embryo development (7).…”
Section: Unraveling the Genetics Of Female Infertilitymentioning
confidence: 63%
“…The PADI family was made up of five members: PADI1, PADI2, PADI3, PADI4 , and PADI6 ( Liu et al, 2021 ). PADI6 was only found in oocytes and early embryos, and it was required for oocyte maturation and embryo development ( Liu et al, 2021 ), and was one of the SCMC components that localized to other components in oocytes and early embryos ( Xu et al, 2016 ; Wang et al, 2022 ). PADI6 encoded a peptidylalarginine deiminase, the amino acid sequence of which was substantially conserved across mammalian peptidylarginine deiminases ( Xu et al, 2016 ; Lu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…PADI6 was considered to encode a protein involved in the SCMC, which was required for embryonic advancement beyond the 2-cell stage ( Li et al, 2010 ). The homozygous mutations and the compound-heterozygous mutations of PADI6 have been reported to cause embryo arrest ( Wang et al, 2022 ; Xu et al, 2022 ). In this case, we found a missense mutation (c. 1247T>C) and a frameshift mutation (c. 2009 2010del) in PADI6 by WES, as well as embryos with aberrant cleavage patterns and embryos at 1- or 2-cell arrest on Day 2.…”
Section: Discussionmentioning
confidence: 99%